Citizen-led Constitutional Reform: Assessing the Promise of Deliberative Democracy - Quill, Ursula (Trinity College Dublin. School of Law. Discipline of Law, 2025)
This thesis analyses the contribution of the Citizens' Assembly on the Eighth Amendment to the referendum on abortion in Ireland in 2018 through an in-depth study of the Citizens' Assembly's relationship to the Oireachtas. I address three main questions through the study. First, why did the Government establish a Citizens' Assembly to address the issues surrounding the Eighth Amendment, and what can that tell us about the relationship between the Houses of the Oireachtas and the Citizens' Assembly? Second, in what ways did the Oireachtas Committee's consideration of the Assembly's report influence the development of a constitutional and legislative proposal in advance of the referendum, and what are the implications of that influence for the legitimacy of the proposal? Third, can the influence of the Assembly be traced at later stages of the referendum, and what can this tell us about the influence of the Assembly on the wider population and on constitutional deliberation more generally? These questions are important given the need to understand the phenomenon of deliberative democracy in Ireland, particularly on sensitive constitutional questions, which has garnered international attention, and to explain the interaction between the Assembly and elected representatives. Methodologically, the thesis takes the form of a detailed case study which addresses several gaps in the literature on deliberative democracy. I begin with an analysis of the key theories of deliberative systems, designed coupling, and constitutional deliberation, to identify why deliberative mini-publics have been established in recent years, particularly in Ireland, and the influence they have had on elected representatives. Two areas arising in the literature could be better understood through the case study: first, the relationship between the Assembly and elected representatives, and second, how the Citizens' Assembly's influence was felt within the political system. The aim of the case study is to enhance scholarly understandings of the referendum on abortion in 2018 by following the connections between the Assembly and the subsequent stages leading to the referendum. I am particularly concerned with the relationship between the Assembly and the parliamentary committee that was established to consider the Assembly's recommendations and report as part of the initiation and agenda-setting stage of the subsequent referendum. I focus on this relationship as an example of designed coupling of discursive sites and examine the extent to which the coupling enhanced the influence of the Assembly's recommendations at a political level. In an important original contribution to existing scholarly literature on the referendum, I draw on insights from interviews with members of the Oireachtas Committee. These show that the process was an example of democratic iteration, in which similar issues could be discussed in different discursive forums by both citizens and political elites, contributing to a deeper understanding of the constitutional and legislative concerns surrounding the referendum. The Oireachtas Committee built on the Citizens' Assembly's deliberations and filled gaps where the Assembly had not had the opportunity to fully explore certain aspects. This iteration was evident across three fundamental areas which were important in forming consensus around the legislative proposal: rape law, abortion pills, and fatal foetal abnormalities. Additionally, both the Citizens' Assembly and Oireachtas Committee drew on similar expert witnesses, some of whom would become spokespeople in the subsequent campaign. Second, the Assembly's deliberations increased the confidence of Oireachtas members and their sense of legitimacy in pursuing a similar route of liberalisation as had been recommended by the Assembly. Third, the Oireachtas report functioned as a bridge between the citizens' deliberations and the government's deliberations which produced the final wording which was put to the people.
APPROVED
Keywords: constitution; reform; democracy; referendum; deliberation; assembly; citizens; vote; government; legislation; abortion; amendment